2022
DOI: 10.3390/su14095317
|View full text |Cite
|
Sign up to set email alerts
|

How Efficient Is the Cohesion Policy in Supporting Small and Mid-Sized Enterprises in the Transition to a Low-Carbon Economy?

Abstract: Funds from the European Union that are devoted to fostering a low-carbon economy are aimed at assisting Member States and regions in implementing the required investments in energy efficiency, renewable energy, and smart distribution electricity grids, and for research and innovation in these areas. In this context, we assessed the implementation of these funds in small and medium-sized enterprises across different beneficiary countries and regions of the European Union. Therefore, this study uses a non-radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Additionally, [62] applied the value-based DEA technique to appraise the execution of ESIF devoted to fostering the competitiveness of SMEs across different OPs (national and regional). In addition, [63] considered the output-oriented version of the slack-based model (SBM) combined with cluster analysis for assessing 102 OPs from 22 EU countries committed to fostering a low-carbon economy in SMEs. Finally, [64] employed the non-oriented version of the network SBM model coupled with cluster analysis to appraise 53 OPs from 19 countries dedicated to promoting research and innovation in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, [62] applied the value-based DEA technique to appraise the execution of ESIF devoted to fostering the competitiveness of SMEs across different OPs (national and regional). In addition, [63] considered the output-oriented version of the slack-based model (SBM) combined with cluster analysis for assessing 102 OPs from 22 EU countries committed to fostering a low-carbon economy in SMEs. Finally, [64] employed the non-oriented version of the network SBM model coupled with cluster analysis to appraise 53 OPs from 19 countries dedicated to promoting research and innovation in SMEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An efficient policy implementation implies an efficient financial execution of OPs, with a particular focus on the pace of execution of the OPs ( [62][63][64]73]). In this context, costs must be certified by an approved authority, which is the entity in charge of certifying that the co-funded equipment/services were supplied, that the corresponding payments were made, and that the payments conformed with the EU and national rules.…”
Section: The Rate Of Ops' Executionmentioning
confidence: 99%
“…The criteria used in this study were suggested by Henriques et al (2022a) at the OP level. The numbers evaluated are total figures at the MS level spanning various years reported on November 19, 2021 (corresponding to the programming period of 2014-2020), because they are the most up-to-date statistics for the accomplishment criteria.…”
Section: Datamentioning
confidence: 99%
“…Simply explained, an LCE is an economy whose organization is sustained by activities that emit minimal quantities of CO 2 into the environment (Levy, 2010). The cohesion policy has been supporting the shift to an LCE, but in the 2014-2020 period this support has expanded dramatically, owing in part to the granting of specific funding for this purpose (Henriques et al, 2022a). As a result, assessment plays an important role in cohesion policy-making since it supports policy planning and development while also delivering solid data about the outcomes and effects of the projects undertaken.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation